Hegel e a refutação do ceticismo - Bisneto, Oscar Cavalcanti de (2007)
The present thesis intends to analize the relationship between Hegelian System and philosophical Skepticism. It focuses Hegel´s interpreteation of Schulzean and Pyrronian Skepticism, as well as his attempt to refute both of them. The main Idea is that Agrippa´s Tropes assume a capital role in the process of justification of the Hegelian Science